2009
DOI: 10.1200/jco.2008.19.9968
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunological Efficacy of a DNA Vaccine Encoding Prostatic Acid Phosphatase in Patients With Stage D0 Prostate Cancer

Abstract: Purpose Prostatic acid phosphatase (PAP) is a prostate tumor antigen. We have previously demonstrated that a DNA vaccine encoding PAP can elicit antigen-specific CD8+ T cells in rodents. We report here the results of a phase I/IIa trial conducted with a DNA vaccine encoding human PAP in patients with stage D0 prostate cancer. Patients and Methods Twenty-two patients were treated in a dose-escalation trial with 100 μg, 500 μg, or 1,500 μg plasmid DNA, coadministered intradermally with 200 μg granulocyte-macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
179
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(189 citation statements)
references
References 22 publications
5
179
1
1
Order By: Relevance
“…However, there are reports of vaccine-induced, antigen-specific CD8 + T cell responses detected by IFN-γ ELIspot against specific peptide pools. 40 In the majority of the clinical trials, the focus is on serum PSA responses, humoral responses as well as T cell activation or CD4-responses. 19 , 28 , 29 , 41-44 No autologous tumors were available from the patients from this trial, making it impossible to test whether the CD8 + T cells recognizing antigens in the UbiLT3 DRibble vaccine could also recognize and kill autologous tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports of vaccine-induced, antigen-specific CD8 + T cell responses detected by IFN-γ ELIspot against specific peptide pools. 40 In the majority of the clinical trials, the focus is on serum PSA responses, humoral responses as well as T cell activation or CD4-responses. 19 , 28 , 29 , 41-44 No autologous tumors were available from the patients from this trial, making it impossible to test whether the CD8 + T cells recognizing antigens in the UbiLT3 DRibble vaccine could also recognize and kill autologous tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Patients received 100, 500, or 1500 μg plasmid intradermally six times at 14-day intervals, with 200 μg GM-CSF co-administered as a vaccine adjuvant, analogous to studies performed in rats. No significant adverse events were detected, and ten of 22 patients generated PAP-specific T-cell responses immediately after immunization [57]. Responses observed were Th1 type, and cytolytic T-cell responses were specifically elicited in HLA-A2-expressing subjects [58].…”
Section: Introduction: Cancer Immunotherapy and Anti-tumor Vaccinesmentioning
confidence: 99%
“…The PSA doubling time was observed to increase from a median of 6.5 mo pretreatment to 8.5 mo on-treatment (P D 0.033), and 9.3 mo in the 1-y post-treatment period (P D 0.054). 25 However, obstacles regarding the application of DNA-based anti-cancer vaccines consist in the risk of integration into the host genome and subsequent malignant transformation, especially when compared with the properties of mRNA. It has been reported that mRNA molecules can activate the innate immune system inducing the maturation of professional antigen presenting cells and the release of cytokines.…”
Section: Nucleotide-based Vaccination Strategies For Prostate Cancermentioning
confidence: 99%